EVALUASI KINERJA PLATE HEAT EXCHANGER DI REFINERY PLANT INDUSTRI MINYAK GORENG - Yahya, Agung Kurnia; Romigo, Rivaldo; Rahayu, Puji; Aini, Apsari Puspita; Ulia, Hasnah (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2023)
Plate Heat Exchanger (PHE) is an element that has an important role in energy efficiency in PT. XYZ. At PT. XYZ there is a problem with the PHE device, where the flow rate of the hot fluid in the device tends to decrease over time, this can cause the heat transfer between the hot fluid and the cold fluid to be sub-optimal resulting in a decrease in the performance of the device. The performance of PHE equipment can be seen from its effectiveness, if PHE performance decreases it can cause an increase in energy consumption so that the cost incurred also increases. This study aims to calculate the effectiveness of PHE type 605A used as a heat exchanger between crude palm oil and bleached palm oil refined at PT. XYZ and current effectiveness is around 81.77% - 86.13%. However, the efficacy of PHE decreases over time and is expected to decrease to 75% on day 11. Recommendations that can be given in this study are routine maintenance and cleaning, real-time monitoring of the performance of the plate heat exchanger, and a review of the workload of the plate heat exchanger system.